Gestational overweight decreased risk of antepartum hemorrhage in pregnant women with complete placenta previa: a retrospective study - Yang,Jie; Ye,Shaoxin; Xuan,Bihua; Liu,Zhengping; Fan,Dazhi (PeerJ, 2025)
Background Antepartum hemorrhage (APH) is associated with perinatal mortality and maternal morbidity. Previous studies have reported that obesity in pregnancy adversely influences both fetal and neonatal outcomes. This study aimed to investigate gestational overweight and the risk of APH in pregnant women with complete placenta previa (CPP). Methods This was a retrospective cohort study of pregnant women with CPP delivery at our hospital from 2013 to 2015. Outcomes were stratified according to APH and non-APH. Results Of 193 pregnancies with CPP, 40.4% (78) were diagnosed with APH. Maternal weight and BMI at delivery were significantly decreased in women with APH (61.15 ± 8.73 vs. 65.22 ± 7.80, 24.47 ± 3.12 vs. 26.21 ± 2.85; P = 0.001, P = 0.001; respectively), and the prevalence of overweight at delivery was higher in the non-APH group compared to those in the APH group (54.9% (62) vs. 39.7% (27); OR 2.18; 95%CI [1.16–4.11]). After adjusting for gestation week and other potential confounding factors, maternal weight and BMI were associated with the APH (OR 0.95, 95%CI [0.91–0.99]; 0.85, 95%CI [0.75–0.97], respectively). Conclusion Appropriate weight gain during pregnancy may decrease the risk of antepartum hemorrhage in pregnant women with complete placenta previa.
Keywords: Antepartum hemorrhage; Gestational overweight; Complete placenta previa; Risk; Pregnancy